IDENTIFIKASI FAKTOR-FAKTOR PENYEBAB PENYIMPANGAN MUTU PRODUK IKAN TERI NASI (STUDI KASUS DI PT. KELOLA MINA LAUT UNIT SUMENEP) - Askur Rahman (Agroindustrial Technology, University of Trunojoyo Madura, 2013)
Quality control is a process to regulate the quality of the product and compare it withcertain standards and perform an action if there are irregularities or omissions. Irregularitiesor negligence caused by a number of factors that need to be traced further. Therefore the aim ofthis research is to identify the cause of deviation factors product quality. Identification offactors cause deviations of quality on this research method using fishbone diagrams. The resultsshowed that factors that influence directly on the fish is not intact, the color of the fish is notappropriate and inappropriate types of fish on the end product is the raw material, human orworkers, methods of work and the environment. Factors that affect the size of the fish is notappropriate is the raw material, human or workers, working methods, machines or equipmentand the environment.